Updating Human Capital Decisions: Evidence from SAT Score Shocks and College Applications - Bond, Timothy N.; Bulman, George; Li, Xiaoxiao; Smith, Jonathan (Journal of Labor Economics, 2018)
We estimate whether students update the colleges to which they consider applying in response to large, unanticipated information shocks generated by the release of SAT scores—a primary factor in admission decisions. Exploiting population data on the timing of college selection and a policy that induces students to choose colleges prior to taking the exam, we find that students update their portfolios in terms of selectivity, tuition, and sector. However, the magnitude of updating is too modest to significantly reduce unexplained variation across students, suggesting that nonacademic factors are the dominant determinants of college match.